Designing An Instrument For Gauging Equity Literacy - N. K. Rathee; Joseph Falodun; Wan Li; Pengyue He; Vikramjit S. Rathee (European Scientific Journal, ESJ, 2023)
Equity literacy refers to the skills and mindsets needed to recognize, respond to, and redress conditions that deny equitable access to education. It involves understanding how identities such as ethnicity, gender, sexual orientation, language, religion, immigration status, and disability intersect and contribute to class inequities. More than mere awareness, equity literacy demands a commitment to deepening individual and institutional understandings of the dynamics of equity and injustice within organizations and communities. Its goal is to pinpoint disparities, eradicate inequities, and actively foster a culture of equity. Evaluating equity literacy is essential to understand how educational disparities impact access to equitable opportunities free from bias and discrimination. Considering the existing deficiency in tools for assessing equity literacy, this study introduces a survey instrument designed to assess equity literacy in educational institutions. This survey was developed based on Gorski's equity literacy framework (2016). To establish its validity, the survey was reviewed by experts and refined using Lawshe’s Content Validity Ratio (CVR). Items with CVR scores below the established threshold were removed. The revised 20-item survey was administered to 34 individuals to assess reliability using Cronbach’s alpha. The survey demonstrated robust reliability with an alpha of 0.87. Additionally, the survey categorizes total scores into four rubric levels of equity literacy: exceptional, fair, developing, and little/none. This survey serves as a foundational tool for implementing this framework,  thus empowering educators to challenge prevailing mindsets and cultural deficits.